ISLAMIC EDUCATION AND MODERN TECHNOLOGIES: POSITIVE AND NEGATIVE IMPACT IN MULTICULTURAL SOCIETY IN INDONESIA - Rini Fitria , Munjiatun Aliah (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Islamic education is not any a whole lot of supported the memorization approach of studying. The schooling house has slowly however sure as taking pictures visible a modification. The long run of training is all concerning personalizing learning, allowing youngsters to discover at their very own tempo and gaining knowledge of fashion. Customized studying might be saved far away from the usage of technology too; however, the utilization of technology amplifies and makes the Islamic education method faster. Despite the fact that era has been regarded as though it Might be a challenge to a toddler’s mastering we’d want to recognize there is no escaping it. Therefore we must continually honestly accept this and strike a stability on however we have a tendency to use it. With the recent dramatic will boom in era, nowadays Islamic education has been changed and affected in ways wherein each effective and bad. At some stage in time as generation unceasingly modifications, accordingly do the methods wherein academics use their classrooms.